2016
DOI: 10.1371/journal.pone.0165587
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe Tobacco Smoking and Gastric Cancer Risk among Vietnamese Men

Abstract: BackgroundThe association of waterpipe tobacco (WPT) smoking with gastric cancer (GC) risk was suggested.MethodsA hospital-based case-control study was conducted to examine the association of WPT with GC risk among Vietnamese men, in Hanoi city, during the period of 2003–2011. Newly-diagnosed GC cases (n = 454) and control patients (n = 628) were matched by age (+/- 5 years) and the year of hospitalization. Information on smoking and alcohol drinking habits and diet including salty food intake and fruits/veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Contrary to common misconception, serious health effects are related to WP use. Epidemiological studies have shown that WP smoking is associated with increased risks of cardiovascular diseases,6 cancer (lung, oesophageal, head and neck, and gastric),7–10 metabolic syndrome11 and chronic obstructive pulmonary disease (COPD) 12. An additional health risk that is of particular concern for young adults is nicotine dependence, and similar to any other tobacco product is represented in WP smokers by substance addiction behaviours 13–19.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to common misconception, serious health effects are related to WP use. Epidemiological studies have shown that WP smoking is associated with increased risks of cardiovascular diseases,6 cancer (lung, oesophageal, head and neck, and gastric),7–10 metabolic syndrome11 and chronic obstructive pulmonary disease (COPD) 12. An additional health risk that is of particular concern for young adults is nicotine dependence, and similar to any other tobacco product is represented in WP smokers by substance addiction behaviours 13–19.…”
Section: Introductionmentioning
confidence: 99%
“…Water-pipe tobacco smoking and the use of smokeless tobacco have been associated with gastric cancer risk in Vietnam and India. 19,20 According to the World Cancer Research Fund (WCRF) panel, alcohol consumption, body fat, and consumption of foods preserved by salting and processed meat are probable risk factors for gastric cancer. 21 Although the vegetable and fruit intake was considered as "probable" protective factors for gastric cancer in the earlier report, the strength of evidence was weakened in the recent report where the evidence on the association of vegetable and fruit intake with gastric cancer was "limited."…”
Section: Introductionmentioning
confidence: 99%
“…Other tobacco‐related products were also found to be associated with GC: Two Asian studies reported an association with tobacco chewing and waterpipe tobacco smoking 23 . Interestingly, vegetable and fruit consumption appears to have a more protective effect among smokers than nonsmokers 24 …”
Section: Primary Preventionmentioning
confidence: 99%